Adenovirus can be a serious, life‐threatening disease, even in previously healthy children. (11th December 2021) - Dotan, Miri; Zion, Elena; Bilavsky, Efraim; Nahum, Elhanan; Ben‐Zvi, Haim; Zalcman, Jonatan; Yarden‐Bilavsky, Havatzelet; Kadmon, Gili
Abstract: Aim: Adenovirus infections are exceedingly common in childhood. However, little is known of the clinical characteristics of children admitted with severe infection to the paediatric intensive care unit (PICU). Methods: Clinical data on children hospitalised with adenovirus infection between January 2005 and March 2020 were collected. We compared data between children hospitalised in the PICU and those who were not in a 1:2 ratio. Results: During the study period, 69 children with adenovirus infection were admitted to the PICU, representing 5% of all hospitalised children with adenovirus. Thirty‐four (49%) were previously healthy children. Mortality occurred in 5 patients, and all had an underlying illness. Cidofovir was used in 21 children, including 11 who were previously healthy. No side effects were attributed to the treatment. During 2005–2014, viral co‐infection rates were 42% in the PICU group and 11% in the control group ( p  = 0.002). However, during 2015–2020, when the viral panel became widespread in our institution, the rates of co‐infection were similar in the two groups (32% and 34%, p = 1.0). Conclusion: Our findings suggest that adenovirus may present as a serious, life‐threatening disease even in previously healthy children.